Pengembangan Sumber Daya Insani Melalui Program Keterampilan di Pondok Pesantren Darul Ulum Kembaran Kalikajar Wonosobo - Ahmad Robihan (Prapanca : Jurnal Abdimas, 2023)
Abstract In the present era, pesantren as Islamic educational institutions, are not only demanded by the scientific transfer of Islam limited to the theory of the book only, but must provide quality and quality education programs for the life of student, based on the background that the authorized the title, Human Resource Development Through Skills Programs In Islamic Boarding Schools Darul Ulum Luwihan Kembaran Kalikajar Wonosobo. The objectives to be achieved in this study are; 1) to find out the development of human resources through skills programs in islamic boarding schools Darul Ulum, 2) To find out quality of human resources in islamic boarding schools Darul Ulum Luwihan Kembaran Kalikajar Wonosobo, 3) to find to the supporting factors, obstacles and solutions in the development of human resources in islamic boarding schools Darul Ulum. This research is descriptive qualitative research, namely research that seeks to describe the state of an object of research based on the quality of the items obtainedin the study. As for the methods usid in collecting data are observation, dokumentation, and interviews. The results of the study show, 1) That the development of human resorces in the Darul Ulum Luwihan Kembaran Kalikajar Wonosobo boarding school through skills programs, among others : speech, cullinary art, tambourine, tilawatil Qur’an, rearding al-berjanjzi, and handicrafts. 2) that the quality of student human resources in the Darul Ulum boarding school is the relatively low, because most student only pass formal education to the elementary and secondary levels, do to know the religious knowledge in depth, and do not have special skills, 3) suppoting factors: student interest is quality large, there are other institutions that are willing to provide training. Barriers invlude; lack of professionals in skills development, utillzation of less than optimal time, bidget, inadequate facilities and infrastrukture. The solution to the existing problems is the needfor the implementation of training that is attended by educators, uti;izing the existing time to the maximum, and working with instotutions or agencies that are not bound.